Research into the Epipelic Diatoms of the Meriç and Tunca Rivers and the Application of the Biological Diatom Index in Water Quality Assessment - Cem Tokatlı; Cüneyt Nadir Solak; Elif Yılmaz; Tahir Atıcı; Hayri Dayıoğlu (Aquatic Sciences and Engineering)
The Meriç River is one of the longest rivers of the Balkans and the Tunca River is the most significant tributary of the Meriç River. In the present study, the epipelic diatoms of the Meriç and Tunca Rivers were investigated and the water quality was evaluated from a physicochemical and biological perspective. Epipelic (EPP) diatoms were collected from the middlestream of the Meriç River (Edirne Province of Turkey) and from the downstream of the Tunca River (before emptying into the Meriç River) and certain physicochemical parameters including dissolved oxygen (DO), oxygen saturation (OS), pH, electrical conductivity (EC), total dissolved solids (TDS), salinity, turbidity, nitrate (NO3), nitrite (NO2), ammonium (NH4), phosphate (PO4), sulphate (SO4), chemical oxygen demand (COD) and oxidation-reduction potential (ORP) were measured during the field studies. The Biological Diatom Index (IBD) was used to determine the trophic status of the Meriç and Tunca Rivers in terms of EPP diatoms, and Cluster Analysis (CA) was applied to the detected biological data in order to classify the identified diatom taxa in terms of their dominance in the system. According to the results of the physicochemical analysis, the Meriç and Tunca Rivers have I. – II. Class water quality in terms of dissolved oxygen, oxygen saturation, pH, EC, TDS, NO3, NH4, SO4 and COD parameters; and have III. – IV. Class water quality in terms of NO2 and PO4 parameters. 24 diatom species were recorded in the Meriç River by counting a total of 403 valves and a total of 19 diatom species were identified by counting a total of 409 diatom valves in the Tunca River. Cyclotella atomus Hustedt, Navicula gregaria Donkin, Nitzschia palea (Kützing) W.Smith and Nitzschia subacicularis Hustedt, were determined as the most dominant species in the Meriç River and Navicula erifuga Lange-Bertalot, Navicula gregaria Donkin and Navicula rostellata Kützing were recorded as the most dominant taxa in the Tunca River. According to the result of the IBD, the investigated rivers were found to be in a meso-eutrophic state and according to the results of CA, three statistical clusters were formed for both rivers, and were named as “dominant taxa”, “frequent taxa” and “rare taxa”.